Hubungan Antara Kepercayaan Diri dengan Penyesuaian Sosial pada Siswa Kelas X SMA Advent 1 Medan - Debby Vivian Siregar; Nafeesa Nafeesa (Tabularasa: Jurnal Ilmiah Magister Psikologi, 2022)
This study aims to see the correlation between self-confidence and social adjustment in class X students of SMA Advent 1 Medan. This research uses the quantitative method. Sampling using total sampling technique. The data collection technique used two Likert scales, namely the Self-Confidence scale and the Social Adjustment scale. The population in this study were 47 students and the number of samples in this study was 47 students of class X SMA. The research instrument is the self-confidence scale and the social adjustment scale. The data analysis method used in this research is Correlation-Product Moment. Based on the calculation of the r Product Moment analysis with a value or coefficient (rxy)= 0,677 and a coefficient (r2) = 0,431 with p = 0.000 0,05. These results indicate that the hypothesis proposed in this study is accepted, namely that there is a relationship between self-confidence and social adjustment. This means that the better the self-confidence, the higher the social adjustment. With the results of the correlation coefficient rxy = 6,77, the level of the relationship between Self-Confidence and Social Adjustment is classified as moderate. Another result of this study is that students' self-confidence is considered high. This is based on the hypothetical mean value of 62,5 than the empirical mean of 74,87. Then it is known that the social adjustment of students is classified as high or positive and is based on a hypothetical mean value of 97,5 than the empirical mean of 122,09.